Caracterização estrutural e potencial antimicrobiano, antiparasitário e antiproliferativo de novos peptídeos análogos da stigmurina - Carmo, Bruno Amorim do (2019)
In the venom of scorpions, it is possible to find a rich source of biologically active components with high potential for therapeutic and biotechnological application, and can be used as prototypes to obtain new drugs. The objective of this study was to characterize the structural conformation, evaluate the antimicrobial, antiparasitic, antiproliferative activities and demonstrate the possible mechanism of action associated to these activities, using the molecular dynamics of two new analog peptides of the Stigmurina scorpion peptide, named StigA25 and StigA31. The amino acid substitutions in the native sequence for lysine residues resulted in peptides with higher positive net charge and hydrophobic moment, with an increase in the theoretical helical content. In the analysis by circular dichroism, the analog peptides presented the ability to modify their structural conformation depending on the medium in which they are found, presenting thermal stability at a wide pH and temperature variation, with similar results for the native peptide. StigA25 and StigA31 demonstrate a broad spectrum of antimicrobial and antiparasitic T. cruzi activity in vitro with an effect superior to the native peptide and reference antibiotics, with a reduced hemolytic effect at concentrations that present biological activity and antiproliferative activity in HeLa cells. Therefore, this study demonstrates the therapeutic potential of such analog peptides and the promising effect of peptide engineering for the potential development of novel therapeutic agents.